Efisiensi Pemanfaatan Radiasi Surya, Pertumbuhan dan Produksi Tanaman Soba (Fagopyrum esculentum Moench.) di Ciawi Bogor - Taufan Hidayat; Yonny Koesmaryono (Jurnal Agrista, 2010)
Solar Radiation Use Efficiency, Growth and Soba (Fagopyrum esculentum Moench.) Production in Ciawi BogorABSTRACT. Soba (Fagopyrum esculentum Moench) is potential alternative food source because of its chemical contents which are not so different from other main food sources. In its agronomical development, intensive and sustain research are needed to study solar radiation uses efficiencies, growth and yield of soba under different population an time planting. This research conducted from April to August 2000 at BPLP Ciawi – Bogor experiment station 415 meter top of sea level, 106 51 BT and 06 38 LS. Unit of research arranged by factorial completely randomized block design. The population factor consist of 3 level : 200 plants m-2 (P1), 160 plants m-2 (P2) and 133 plants m-2 (P3), and time of planting also consist of 3 levels : on April (T1), May (T2) and June (T3). Solar radiation uses efficiency at early growth to weeks after planting was higher at high population compared to low population, but after 5 weeks of planting or when maximum efficiencies, its higher on P2 compared P3 and P1. This showed that when grain filling and maturing, it is more intensive on low population then high population, however the anova for two factors at maximum efficiencies did not showed significant differences. Growth and yield of soba is better on high population compare to low population. This because on high population the microclimate condition and water availability is more adequate then on low population. There was no significant different on 1000 grain weight caused by two factors. For total yield P1 172,1 gm-2 was highest and significantly different then P2 143,6 gm-2 and P3 123,9 g m-2. Production cause by time of planting did not showed significant different between T1 and T2 but it did on T3.